Nonfarm Income, Inequality, and Poverty in Rural Egypt and Jordan - Adams, Richard H. (World Bank, Washington, DC, 2014)
The rural economy of developing countries has long been regarded as synonymous with agriculture but in recent years this view has begun to change. Such diverse activities as government, commerce, and services are now seen as providing most income in rural households. Applying decomposition analysis to two new nationally representative sets of household data from Egypt and Jordan, the author examines how different sources of income--including nonfarm income--affect inequality in rural income. He concludes: 1) Nonfarm income has different impacts on poverty and inequality in the two countries. In Egypt the poor (those in the lowest quintile) receive almost 60 percent of their per capita income from nonfarm income. In Jordan the poor receive less than 20 percent of their income from nonfarm income. So nonfarm income decreases inequality in Egypt and increases it in Jordan. 2) Access to land accounts for this difference between the two countries. In Egypt the cultivated land base is totally irrigated and very highly productive. Egypt's large rural population seeks access to land but because the land-to-people ratio is so unfavorable, only a minority of rural inhabitants actually own land. The rest--especially the poor--are forced to seek work in the nonfarm sector. By contrast, only 30 percent of Jordan's cultivated land base is irrigated and crop yields are low. So Jordan's rural population does not press for access to land because the attractive economic rates of return are found in the non-farm sector. Unlike Egypt's rich, rural Jordan's rich earn less than 10 percent of their total per capita income from agriculture and more than 55 percent of it from non-farm sources. 3) The poor in both countries depend heavily on government employment to decrease inequality. Government wages provide 43 percent of non-farm income for Egypt's rural poor and 60 percent of Jordan's. But since both governments already employ far more workers than they can possibly use, advocating increased government employment to reduce inequality would not be wise policy advice. From a policy standpoint, it would be better to reduce income inequality by focusing on non-farm unskilled labor (for example, in construction, brick-making, and ditch-digging), an important income source. 4) In Egypt non-farm income decreases inequality because inadequate access to land "pushes" poorer households out of agriculture and into the non-farm sector. Although agricultural income is positively associated with land ownership in rural Egypt, that ownership is unevenly distributed in favor of the rich, so nonfarm income is not linked to land ownership and is thus more important to the rural poor.